2013
DOI: 10.2903/j.efsa.2013.3267
|View full text |Cite
|
Sign up to set email alerts
|

Technical specifications on harmonised epidemiological indicators for biological hazards to be covered by meat inspection of farmed game

Abstract: In this report, harmonised epidemiological indicators are proposed for foodborne biological hazards to public health that are related to farmed game and meat thereof and that can be addressed within meat inspection. These hazards include Salmonella, Toxoplasma, Trichinella and Mycobacterium in farmed wild boar and deer. An epidemiological indicator is defined as the prevalence or concentration of the hazard at a certain stage of the food chain or an indirect measure of the hazard that correlates to the human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…To lower the prevalence of Salmonella spp. in "farmed" game meat, an integrated approach is suggested, with the application of indicators of specific harmonized epidemiological indices [43]. Further studies are therefore needed to define whether, in a "forest to fork" approach, similar indices could be implemented for certified wild boar meat to reduce the levels of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…To lower the prevalence of Salmonella spp. in "farmed" game meat, an integrated approach is suggested, with the application of indicators of specific harmonized epidemiological indices [43]. Further studies are therefore needed to define whether, in a "forest to fork" approach, similar indices could be implemented for certified wild boar meat to reduce the levels of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Wild boars can serve as reservoirs for a range of pathogens, some of which are transmissible to domestic animals and humans, representing a potential veterinary and Animals 2021, 11, 2227 2 of 8 public health threat [3]. Toxoplasma gondii and Salmonella rank among the most important pathogens at the wildlife-livestock interface [4] and are listed as foodborne biological hazards related to game and game meat [5].…”
Section: Introductionmentioning
confidence: 99%
“…are gram-negative enteric bacteria and belong to the most important etiological agents of foodborne diarrheal diseases worldwide [11,12]. Wild boars may be carriers of various Salmonella enterica serovars, including S. enteritidis and S. typhimurium, which are most frequently implicated in human illness in Europe [5,13], and S. cholerasuis, which is a swine-adapted serovar infrequently reported among domestic pigs in Europe, but considered a major problem for the pig industry in North America and Asia [14]. Various studies estimate the seroprevalence of Salmonella among wild boar in Europe to be between 4% and 19% [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies worldwide have shown a general downward tendency in the prevalence of T. gondii presumably related to improved biosecurity related to indoor housing systems. In organic and free-range pigs, seroprevalences between 1% and 25% have been reported (Kijlstra et al, 2004;van der Giessen et al, 2007;Dubey et al, 2008), while seroprevalences between 7% and 49% were described in European studies of wild boars (EFSA, 2013b;Dubey et al, 2014). In fattening pigs, on the other hand, a seroprevalence of around 2% has been found repeatedly in intensive farming systems around the world (Patton et al, 2002;de Buhr et al, 2008;Dubey et al, 2014).…”
Section: Toxoplasma Gondii In Pigs and Wild Boarmentioning
confidence: 99%
“…It is not feasible to monitor all pigs used for human consumption for infection with T. gondii, and monitoring should focus on free-range pigs, pigs from organic farms, and farmed wild boar, since they are more likely to be exposed to the infection compared to pigs conventionally reared indoors (EFSA, 2007(EFSA, , 2013b. It is not feasible to monitor all pigs used for human consumption for infection with T. gondii, and monitoring should focus on free-range pigs, pigs from organic farms, and farmed wild boar, since they are more likely to be exposed to the infection compared to pigs conventionally reared indoors (EFSA, 2007(EFSA, , 2013b.…”
Section: Diagnosis Including Sampling and Surveillancementioning
confidence: 99%